Hybrid Learning: An Alternative Learning Approach in the Pandemic COVID-19 - Aulia, Roisatul; Sa’idah, Nusrotus (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to describe the implementation of hybrid learning at UNISNU Jepara based on student perceptions. The survey method was used in this quantitative descriptive study. Data was taken through an online questionnaire in the form of 10 closed statements, which were distributed to the sample, namely 40 semester 5 students of the PAI Study Program at UNISNU Jepara. The test results show that the implementation of hybrid learning is well scheduled and effective so that learning objectives can be achieved, as evidenced by the average of 13% of students answering "strongly agree," 47% agree, 35% are unsure, 4% disagree, and 1% strongly disagree. Based on this, it can be concluded that hybrid learning is the right lecture model solution for the COVID-19 pandemic.